Comparative Analysis of Pattern of Symptoms of Chest Pain in Patients with and without Diabetes: A Systematic Review - Syed Azizur Rahman; Satwat Maitra (Journal of Diabetology)
Background: Chest pain is a key indicator and is one of the most frequent complaints in hospital settings. However, atypical presentations of chest pain are often associated with various diseases. The symptoms of chest pain can be particularly ambiguous due to various factors, including gender, diabetes mellitus (DM), and other clinical conditions. Thus, this review performed a comparative analysis of patterns of chest pain in patients with and without DM. Materials and Methods: The review was carried out using electronic databases including PubMed, Scopus, Wiley, and Google Scholar. The studies which were available in the last 10 years from January 2013 to December 2023 were considered. Moreover, the included studies were evaluated using the RevMan 5.4 to analyze the risk of bias. Results: Ten studies were incorporated. The comparative analysis of chest pain patterns reveals that diabetic patients often experience atypical symptoms compared to non-diabetic individuals. The assessment of risks in the study revealed that 58.33% were categorized as having a low risk, while 20% had an unclear risk and 71.67% of cases were classified as not applicable. Conclusion: Chest pain was more prevalent in non-diabetic patients, particularly in AMI and ACS, where they typically presented with classic symptoms. Diabetic patients presented atypical symptoms, such as dyspnea, shoulder pain, gastric discomfort, and cold sweats, complicating timely diagnosis. Comorbidities such as hypertension and angina in diabetic patients further obscured symptom interpretation, increasing the risk of delayed recognition and poorer outcomes.